PHYSICAL FITNESS OUTCOMES RESPONSES TO CIRCUIT RESISTANCE TRAINING – A RANDOMIZED CONTROLLED TRIAL - Jithin Das, T. K.; Sigamani, Jayasingh Albert Chandrasekar (Rehabilitation and Recreation, 2025)
Purpose. This research study was conducted to identify the effect of circuit resistance training on selected physical fitness outcomes among women volleyball players. Materials and methods. 24 players were considered as a sample for this study. The participants were randomly assigned into two groups namely experimental group (n=12) and the control group (n=12). The training program was given to the experimental group for 8 weeks and 3 day per weeks, 60–65 minutes per session. The Control group did not participate in the training designed for this study but they engage in regular volleyball training program. The variables of the study were measured twice, once before the training and then after the training. The results of a statistical analysis comparing the experimental group and the control group on four variables.Results. Paired sample t-test was showed significant difference on physical fitness among the experimental group. The statistical analysis revealed that after eight weeks of CRT there have significant increase in chosen variable such as muscular strength (t = 14.182, df = 11, p = .000), upper body strength (t = 6.588, df = 11, p = .000), explosive power (t = 10.776, df = 11, p = .000), and core stability (t = 5.089, df = 11, p = .000) in the experimental group when compared to control group.Conclusions. The study’s findings concluded that 8 weeks of circuit resistance training significantly improved in physical fitness outcomes, like muscular strength, upper body strength, explosive strength, and core stability in volleyball players, when compared to the control group.